Etiology of neonatal seizures and maintenance therapy use: a 10-year retrospective study at Toulouse Children's hospital - E. Baudou; C. Cances; C. Dimeglio; C. Hachon Lecamus (BMC, 2019)
Abstract Background No guidelines exist concerning the maintenance antiepileptic drug to use after neonatal seizures. Practices vary from one hospital to another. The aim of this study was to investigate etiologies and to report on the use of maintenance antiepileptic therapy in our population of full-term neonates presenting neonatal seizures. Methods From January 2004 to October 2014, we retrospectively collected data from all full-term neonates with neonatal seizures admitted to the Children's Hospital of Toulouse, France. Results Two hundred and forty-three neonates were included (59% males, 48% electroencephalographic confirmation). The frequencies of etiologies of neonatal seizures were: hypoxic-ischemic encephalopathy (HIE) (n = 91; 37%), ischemic infarction (n = 36; 15%), intracranial hemorrhage (n = 29; 12%), intracranial infection (n = 19; 8%), metabolic or electrolyte disorders (n = 9; 3%), inborn errors of metabolism (n = 5; 2%), congenital malformations of the central nervous system (n = 11; 5%), epileptic syndromes (n = 27; 12%) and unknown (n = 16; 7%). A maintenance therapy was prescribed in 180 (72%) newborns: valproic acid (n = 123), carbamazepine (n = 28), levetiracetam (n = 17), vigabatrin (n = 2), and phenobarbital (n = 4). In our cohort, the choice of antiepileptic drug depended mainly on etiology. The average duration of treatment was six months. Conclusions In our cohort, valproic acid was the most frequently prescribed maintenance antiepileptic therapy. However, the arrival on the market of new antiepileptic drugs and a better understanding of the physiopathology of genetic encephalopathies is changing our practice. Trial registration Retrospectively registered. Patient data were reported to the "Commission Nationale Informatique et Libertés" under the number 2106953.